(untitled) (Medical Forum Monthly, 2021)
Objective: To analyse the average ischemia time in Non-ST-elevation myocardial infarction in comparison of ST-elevation myocardial infarction among local population of Pakistan. Study Design: Comparative Study Place and Duration of Study: This study was conducted at the Allama Iqbal Memorial Teaching Hospital Sialkot during June 2020 till December 2020. Materials and Methods: The data was collected 100 patients of both genders. The data was divided into two groups. Results: The data was collected from 100 patients. The mean age of the patients was 51.3 ± 11.5 years in STEMI patients and 57.4 ± 9.4 in NSTEMI. 45 (45%) have diabetic history with STEMI and 55 (55%) with NSTEMI patients. 81 (81%) have smoking history and 17 (17%) have family history of CVD with STEMI. All the data is represented in table 1. Conclusion: It is concluded that there is no difference among the heart rate variability indices in Ischemic heart disease, MI, age group and gender.